TVDD: topology based vehicular data dissemination scheme for stability optimisation in IoV. (22nd April 2021) - Sharma, Richa; Sharma, T.P.; Sharma, Ajay K.
Internet of vehicles (IoVs) nowadays has opened the door to a myriad of advancements in safety, mobility, and in environmental aspects. Although, due to core challenges like high mobility, variable density, frequent fragmentation and the hostile terrain types in vehicles, there is a greater need to improve data dissemination interfaces for the IoV. To mitigate these challenges, this paper proposes an efficient group based topology management vehicular data dissemination (TVDD) scheme that focuses on improving the stability of groups and meeting users' quality of service (QoS) requirements. Continuous service availability is achieved by grouping vehicles in intra-grouping and inter-grouping domains. Group heads (GHs) are selected for avoiding continuous connectivity voids by optimising the stability factor. Furthermore, for holistic data delivery a hybrid data forwarding approach based on LTE-V is proposed. Simulations are carried out using network simulator (NS3) and mobility simulator simulation mobility (SUMO). Encouraging results are obtained in terms of grouping overhead, grouping stability and packet delivery ratio stable data delivery.